Health risk assessment of electronic cigarette use among adults in Klang Valley, Malaysia - Zulkifli, Aziemah; Zainal Abidin, Emilia; Zainol Abidin, Najihah; Praveena, Sarva Mangala; Mohd Ghazali, Hasanah; Amer Nordin, Amer Siddiq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The electronic cigarette (EC) usage has raised public health concerns; whether its advantages to smokers as a potential smoking cessation aid have outweighed its negative health impacts among EC users. This study aims to estimate health risks associated with chemical exposures to nicotine, propylene glycol (PG) and selected Tobacco-Specific Nitrosamines (TSNAs) namely 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and N’-nitro-sonornicotine (NNN) in e-liquids locally-manufactured in Malaysia. Methods: The health risk assessment (HRA) was performed using established guideline by the Environmental Protection Agency (EPA). The average daily dose (ADD) and lifetime average daily dose (LADD) were calculated using previously published data on chemical concentration of selected compounds and local EC usage topography data. Next, the non-carcinogenic risk (nicotine and PG) and carcinogenic risk (NNK and NNN) were calculated and denoted as total hazard quotient (HQT) and total lifetime cancer risk (LCRT) value, respectively. Results: For non-carcinogenic risk, the mean of HQT was 78.9 which falls under “unacceptable” risk as demonstrated by HQT value of more than 1. While for carcinogenic risk, the mean of total LCRT value was 1.54E-04 which may place EC users at risk of developing cancer resulted from exposure to selected TSNAs. Conclusion: Comprehensive HRA using currently available data of local EC usage topography and chemical evaluation of Malaysian-made e-liquids have revealed that the exposure to nicotine, PG and selected TSNAs are expected to be a significant health concern for local EC users. This finding supports the local health authority to issue a stringent health policy in considering EC as a tool for smoking cessation among heavy smokers.